Treatment of epilepsy: the GABA-transaminase inhibitor, vigabatrin, induces neuronal plasticity in the mouse retina - Wang, Qing-Ping (2008)
Vigabatrin was a major drug in the treatment of epilepsy until the discovery that it was associated with an irreversible constriction of the visual field. Nevertheless, the drug is still prescribed for infantile spasms and refractory epilepsy. Disorganization of the photoreceptor nuclear layer and cone photoreceptor damage have been described in albino rats. To investigate the vigabatrin-elicited retinal toxicity further, we examined the retinal tissue of albino mice treated with two vigabatrin doses. The higher dose did not always cause the photoreceptor layer disorganization after 1 month of treatment. However, it triggered a massive synaptic plasticity in retinal areas showing a normal layering of the retina. This plasticity was shown by the withdrawal of rod but not cone photoreceptor terminals from the outer plexiform layers towards their cell bodies. Furthermore, both rod bipolar cells and horizontal cells exhibited dendritic sprouting into the photoreceptor nuclear layer. Withdrawing rod photoreceptors appeared to form ectopic contacts with growing postsynaptic dendrites. Indeed, contacts between rods and bipolar cells, and between bipolar cells and horizontal cells were observed deep inside the outer nuclear layer. This neuronal plasticity is highly suggestive of an impaired glutamate release by photoreceptors because similar observations have been reported in different genetically modified mice with deficient synaptic transmission. Such a synaptic deficit is consistent with the decrease in glutamate concentration induced by vigabatrin. This description of the neuronal plasticity associated with vigabatrin provides new insights into its retinal toxicity in epileptic patients.